Developmental evolution. Issue 1 (1st December 2016) - Lickliter, Robert
Abstract : Biologists and psychologists are re‐thinking the long‐standing premise of genes as the primary cause of development, a view widely embraced in 20th‐century biology. This shift in thinking is based in large part on: (1) the growing appreciation of the complex, distributed regulatory dynamics of gene expression; and (2) the growing appreciation of the probabilistic, contingent, and situated nature of development. We now appreciate that what actually unfolds during individual development represents only one of many possibilities. This expanded focus on the developmental process, often referred to as a developmental systems approach, has far‐reaching implications for developmental and evolutionary theory, including new ways of thinking about the consequences of activity and experience, the emergence of novel properties or traits, the nature and extent of heredity, and the origins of phenotypic variability. WIREs Cogn Sci 2017, 8:e1422. doi: 10.1002/wcs.1422 This article is categorized under: Cognitive Biology > Genes and Environment Neuroscience > Development Neuroscience > Plasticity